PROFESI, PROFESIONAL DAN PEKERJAAN - Amir Sahaka (Jurnal Teknologi Pendidikan Madrasah, 2019)
Today there is a fondness in society to demand professionalism at work. The broader this joy, so the impression arises that this term is used haphazardly without clear concept. It's not uncommon for someone to easily say that what's important is to be professional. But when asked about what is meant by a professional, he cannot give a clear answer. What's interesting is that the word professionalism is apparently not only used for jobs that have been recognized as a profession, but in almost every job. In layman's language, all work (vocation) is then referred to as a profession. Someone is called a professional if the way it works is good, deft, and the results are satisfactory. With the results of his work, someone gets a reward (salary / wage).